Pengaruh Pengeluaran Pemerintah terhadap Tingkat Kemiskinan Melalui Indeks Pembangunan Manusia (IPM) Di Provinsi Jambi Tahun 2017-2021 - Siti Maisaroh (Universitas Batanghari Jambi, 2022)
Increasing human development in a region is influenced by government spending in both the education and health sectors. This also affects the poverty level of a region. This study aims to determine: (1) The effect of government spending on education and health simultaneously on poverty levels through the Human Development Index in Jambi Province. (2) The partial effect of government spending on education and the health sector on the poverty rate through the Human Development Index in Jambi Province. (3) The effect of government spending on Education, Health and Human Development Index simultaneously on the poverty rate in Jambi Province. (4) The partial effect of government spending on Education, Health and Human Development Index on the poverty rate in Jambi Province. The population in this study consisted of 9 districts and 2 cities in Jambi Province in 2017-2021. The type of data used is secondary data, obtained from the Central Bureau of Statistics (BPS) and the Directorate General of Fiscal Balance (DJPK). This study uses simple linear regression analysis and multiple linear regression. Test the prerequisites for data analysis using the normality test, multicollinearity test, and heteroscedasticity test. The results of the study show that: (1) Government spending on education has a significant and significant effect on the Human Development Index (IPM) in Jambi Province in 2017-2021. Meanwhile, the government spending variable in the health sector has no effect on the Human Development Index (IPM) in Jambi Province in 2017-2021. (2) Government expenditure in the education and health sectors has a simultaneous and significant effect on the Human Development Index (IPM) in Jambi Province in 2017-2021. (3) Government spending on education has no effect on the poverty rate, government spending on health has an effect on the poverty rate and the human development index has no effect on the poverty rate in Jambi Province in 2017-2021. (4) Government spending on education, the health sector and the human development index have a simultaneous and significant effect on the poverty rate in Jambi Province in 2017-2021.